2007
DOI: 10.1182/blood-2007-02-075069
|View full text |Cite
|
Sign up to set email alerts
|

Gene mapping and expression analysis of 16q loss of heterozygosity identifies WWOX and CYLD as being important in determining clinical outcome in multiple myeloma

Abstract: We performed fluorescent in situ hybridization (FISH) for 16q23 abnormalities in 861 patients with newly diagnosed multiple myeloma and identified deletion of 16q [del(16q)] in 19.5%. In 467 cases in which demographic and survival data were available, del(16q) was associated with a worse overall survival (OS). It was an independent prognostic marker and conferred additional adverse survival impact in cases with the known poor-risk cytogenetic factors t(4;14) and del(17p). Gene expression profiling and gene map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 44 publications
6
112
0
1
Order By: Relevance
“…Additional studies have associated Cyld downregulation with the development of other types of human cancer including tumors of colon, lung and kidney, as well as melanomas and cervical and hepatocellular carcinomas (Strobel et al, 2002;Hashimoto et al, 2004;Hirai et al, 2004;Costello et al, 2005;Hellerbrand et al, 2007;Keats et al, 2007;Zhong et al, 2007;Massoumi et al, 2009). In the case of multiple myeloma and melanoma, it has been shown that its grade of malignancy is directly related with the silencing of CYLD, being of poor prognosis those tumors with lower expression level of CYLD (Annunziata et al, 2007;Jenner et al, 2007;Massoumi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have associated Cyld downregulation with the development of other types of human cancer including tumors of colon, lung and kidney, as well as melanomas and cervical and hepatocellular carcinomas (Strobel et al, 2002;Hashimoto et al, 2004;Hirai et al, 2004;Costello et al, 2005;Hellerbrand et al, 2007;Keats et al, 2007;Zhong et al, 2007;Massoumi et al, 2009). In the case of multiple myeloma and melanoma, it has been shown that its grade of malignancy is directly related with the silencing of CYLD, being of poor prognosis those tumors with lower expression level of CYLD (Annunziata et al, 2007;Jenner et al, 2007;Massoumi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have focused our attention to the study of the possible involvement of CYLD in skin tumor progression, as this gene has been implicated in the progression of different cancer cell types such as melanoma, colon, hepatocellular and multiple myeloma (Annunziata et al, 2007;Hellerbrand et al, 2007;Jenner et al, 2007;Massoumi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…5 Using this approach we identified the importance of CYLD deletion and mutation while others identified deletion of TRAF2, BIRC2, and BIRC3 that when considered together are consistent with activation of the nuclear factor-B (NF-B) pathway in a proportion of myeloma cases. [6][7][8] Information on CNAs in myeloma samples have been reported using karyotyping, fluorescence in situ hybridization (FISH), array comparative genomic hybridization (aCGH), and SNP-based arrays. 6,[8][9][10][11][12][13] However, to date there have been no detailed reports of CNAs in myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high levels of USP17 have been identified in primary lung, colon, esophagus and cervix tumor biopsies (McFarlane et al, 2010). Furthermore, USP15 is downregulated in paclitaxelresistant ovarian cancer (Xu et al, 2009), and CYLD in melanoma and other malignant tumors (Hellerbrand et al, 2007;Jenner et al, 2007;Massoumi et al, 2009;Gilbert et al, 2011). Finally, A20 expression is also downregulated in some types of lymphoma (Durkop et al, 2003).…”
Section: Genetic or Functional Alterations Of Dubs In Cancermentioning
confidence: 99%